2014
DOI: 10.2298/ciceq120707120p
|View full text |Cite
|
Sign up to set email alerts
|

Photographic study of bubble departure diameter in saturated pool boiling to electrolyte solutions

Abstract: Article Highlights• Larger bubbles are generated in electrolyte solutions compared with water at similar conditions • Increasing the salt concentrations makes the bubbles slightly larger • Bubble diameter decreases with increasing heat flux in all three electrolyte solutions • Larger bubbles appear during boiling of NaCl solutions since it has higher surface tension Abstract Bubble departure diameters during saturated pool boiling to pure water and three different electrolyte solutions including NaCl, KNO 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…They indicated that the bubbles are suppressed by increasing fluid flow rate and inlet subcooling. Recently, Peyghambarzadeh et al (2012) investigated pool boiling heat transfer to NaCl, KNO3, and KCl solutions. The effects of heat flux and salt concentration and also the influences of the physical properties of the solutions on the bubble size were also investigated.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They indicated that the bubbles are suppressed by increasing fluid flow rate and inlet subcooling. Recently, Peyghambarzadeh et al (2012) investigated pool boiling heat transfer to NaCl, KNO3, and KCl solutions. The effects of heat flux and salt concentration and also the influences of the physical properties of the solutions on the bubble size were also investigated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of the inadequacy of this critical information, a theoretical model for prediction of the nucleate boiling heat transfer coefficient is still at the early stage of development. (Gorenflo et al, 1990(Gorenflo et al, , 1998(Gorenflo et al, , 2004Peyghambarzadeh et al, 2009;Hu et al, 2013;Lee et al, 2014;Rocha et al, 2013). In comparison to pool boiling of organic liquid mixtures, far less information is available about the effect of dissolved salts on the mechanisms of boiling.…”
Section: Introductionmentioning
confidence: 99%
“…Hamzekhani等人 [10] 在不同工质气泡脱 离直径的研究中发现, 一定热流密度下, 去离子水、乙 醇及其混合物中较容易出现球形气泡, 这是由于其 直径较小. Peyghambarzadeh等人 [11] 池沸腾研究发现, NaCl溶液中气泡形状基本为球形, KCl和KNO 3 溶液 中出现了扁圆、半球和不规则形状. Kim等人 [12] 发现 压力影响气泡脱离特征.…”
Section: 论 文unclassified
“…This correlation predicts the bubble diameter specifically for electrolyte solutions. Peyghambarzadeh et al (2012) have a wide-ranging survey on some correlations in this field.Due to the fact that pool boiling is of high importance, especially in industry, this paper was experimentally conducted to study bubble departure diameters during saturation pool boiling heat transfer under atmospheric pressure to water, ethanol and methanol pure liquids. Fig.1 schematically demonstrates the experimental equipment used in the present investigation.…”
Section: Introductionmentioning
confidence: 99%